Hoxb6 can interfere with somitogenesis in the posterior embryo through a mechanism independent of its rib-promoting activity - Casaca, Ana (2016)
Formation of the vertebrate axial skeleton requires coordinated Hox gene activity. Hox group 6 genes are involved in the formation of the thoracic area owing to their unique rib-promoting properties. Here we show that the linker region (LR) connecting the homeodomain and the hexapeptide is essential for Hoxb6 rib-promoting activity in mice. The LR-defective Hoxb6 protein was still able to bind a target enhancer together with Pax3, producing a dominant-negative effect, indicating that the LR brings additional regulatory factors to target DNA elements. We also found an unexpected association between Hoxb6 and segmentation in the paraxial mesoderm. In particular, Hoxb6 can disturb somitogenesis and anterior-posterior somite patterning by dysregulation of Lfng expression. Interestingly, this interaction occurred differently in thoracic versus more caudal embryonic areas, indicating functional differences in somitogenesis before and after the trunk-to-tail transition. Our results suggest the requirement of precisely regulated Hoxb6 expression for proper segmentation at tailbud stages.